Pengembangan Usaha Minyak Kelapa Tradisional untuk Meningkatkan Pendapatan IKM Desa Posso, Kabupaten Gorontalo Utara - Rosdiani Azis; Ingka Rizkyani Akolo; Moh. Fikri Pomalingo; Ikrima Staddal (Institut Pertanian Bogor, 2020)
Posso is one of the villages which is located in Kwandang sub-district, North Gorontalo, Province of Gorontalo. It has the potential of coconut plantations with a production capacity of around15,000 coconuts/month. In order to increase the potential of village, the government formed a jointly successful SMEs that are produces traditional coconut oil. The purpose of this activity is to develop a traditional coconut oil business to increase SMEs incomes. The method applied are technology transfer, provision of tools, application of technology and production assistance. Based on the results showed activities obtained training results of packaging design and packaging process that is good and proper nd business management can improve partners' skills in designing attractive packaging and able to manage this business. After this coconut oil business development’s activity, it produced knowledge about the fermentation method in making oil, how to operate coir peeling tools with a chicken paw method, management of a traditional coconut oil processing business, and an increase in partner assets which oil production increased to 150 L or around 200 bottles a month. Overall, this program is well implemented and has benefits for SMIs, especially in developing a successful SME business together.